Analisis Penggunaan Aplikasi Kasir “Majoo” Dalam Sistem Informasi Penerimaan Kas di Mencari Kopi - Della Puspita; Jamil Azhari; Rera Zetira; Dinda Ayu Alifia; Nita Syahputri (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This research aims to analyze the use of the cashier application software "Majoo" in the cash receipt information system Mencari Kopi. The object of this research is the use of the cashier application in cash receipts in Mencari Kopi. The subjects in this research were employees, owners of Mencari Kopi and consumers of Mencari Kopi. This research uses primary data used in this research, namely the source comes from the finance department through observations, interviews and documentation carried out on employees or owners of Mencari Kopi and consumers of Mencari Kopi who pay by cash or digital wallet (e-wallet). ). Secondary data used in this research are documents or notes regarding cash receipts and presentation when using the cashier application on Mencari Kopi. The results of this research. The cash receipt system at Mencari Kopi is run with the help of the “Majoo” cashier application system. The results of the research that has been carried out, in recording cash receipts, payments via cash and non-cash (e-wallet) are equally efficient as long as you still use the "Majoo" cashier application. The results of research conducted and interviews by users of the cashier application and consumers of Mencari Kopi, the recording of cash receipts recorded in Mencari Kopi and those received by consumers of Mencari Kopi are appropriate.